Optimizing the Performance of Satintelkam Polres Pekalongan District in Early Detection to Prevent the Crime of Theft with Weight - Gunawan, Randy (Advances in Police Science Research Journal, 2024)
Theft by weighting is a theft that in its implementation accompanied by certain conditions or actions that can be burdensome. Referring to Article 363 of the Criminal Code, a criminal offense is said to be burdensome if carried out in certain circumstances, including committing livestock theft, theft at the time of fire, eruption, flood, earthquake, volcanic erupting, ceramic ships, stranded ships, train accidents, riots, rebellion or danger of war. According to data on criminal acts at the Pekalongan District Police in 2018-2021, the level of criminal acts of theft by weighting, theft by violence, and theft of motorized vehicles, robbery, and deprivation are still high, causing concerns about the surrounding community and disturbing the security and order of the public. The purpose of this study was to examine the performance of the Pekalongan District Police Intelligence Unit through DII detection in order to prevent criminal acts of theft by weighting in the Pekalongan District Police jurisdiction. This research uses a qualitative approach. In this study, the authors use the type of descriptive analysis. Data collection techniques used are observation, interviews, and document studies. The results of this study indicate that early detection of intelligence is considered good through the planning process compiled from making intelligence administration, organizing with other technical functions during work, intelligence networks as the eyes and ears of members in the field, and direct roles by the leadership in the supervision and control of members in the field. Satintelkam’s management performance system in early detection can be improved through the development of organizational resources for the better. Organizational resources in early detection to prevent criminal acts of theft by weighting are the most important elements in every investigation, security, and raising activities. The need for synchronization between elements that exist in organizational resources to support every investigation activity.